Lipid-lowering activity of mulberry seed unsaturated fatty acids: integrating network pharmacology and experimental validation - Yue Zhang; Haoran Huang; Jianglong He; Yuqi Li; Xueping Jiang; Ping Wu; Syed Asim Shah Bacha; Ran Zhang; Hao Li; Gaiqun Huang; Zhongzheng Gui (Functional & Integrative Genomics, 2026)

Process-aware SSA-Conv-PatchTST for robust multi-horizon aeration-demand forecasting in full-scale wastewater treatment plants - Ran Song; Xiaole Mei; Xinhua Jiang; Xuelei Ma; Muqier Wudan; Wenlong Bai; Hao Lin; Zhi Li; Shengbin Gao (Journal of Water Process Engineering, 2026)

Quantifying hydrological responses to climate change and associated canopy variability using an integrated LSTM-SWAT modeling framework - Kunhao Jiang; Hui Ran; Xinyi Chen; Yingnan Wei; Yuanxin Dai; Qiang Yu; Hao Feng; Xiaotao Hu; Ning Yao (Journal of Hydrology, 2026)

RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Probiotic Bacillus strains enhance cellulose digestibility and silkworms growth via gut microbiota modulation - Yueqin Jin; Ying Zhao; Chen Chen; Xueping Jiang; Sitong Chen; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Insect Physiology, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

pH-responsive metal–organic framework–iron scaffolds for antibacterial and osteogenesis-promoting applications in diabetic infected bone defects - Yaxin Xue; Xinyu Ran; Danyang Zhao; Jian Wang; Hao Jiang; Chengji Wang; Wei Xu; Hao Lv; Zhencheng Yu; Zijing Du; Yi Cao; Dongmei Dong; et al. (Chemical Engineering Journal, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Exogenous microbial agents interact with housefly larvae to reshape the microbiome and accelerate cellulose degradation in silkworm (Bombyx mori) excrement - Chen Chen; Yuanhao Zhang; Yueqin Jin; Jieling Zhou; Xueping Jiang; Sitong Chen; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Insect Physiology, 2026)

Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

Metal-air fuel cells for phosphorus recovery from wastewater: A critical analysis of principles, progress, and application perspectives - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Yuan Liu (Chemical Engineering Journal, 2026)

Research on dual-model collaborative optimization method for intelligent fault diagnosis of nuclear main pump rotor under constant speed and variable speed conditions - Wen-hao Ran; Hong Xia; Xue-ying Huang; Wen-zhe Yin; Pei-qi Jiang (Annals of Nuclear Energy, 2026)

Construction of Li1-xMn2O4-Pb composite electrode ESIX system for efficient lithium recovery from high-sodium sulfate-type lithium-precipitation mother liquor - Jialu Chen; Jiang Gao; Ran Zhang; Zirui Wang; Qiang Ren; Fengfeng Gao; Zhonglin Zhang; Xiao Du; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Photothermal-responsive Au nanorod-silica nanocomposite with on-demand curcumin release for sequential therapy of biofilm infections - Wenhui Jiang; Shunlan Luo; Kehan Du; Kai Yuan; Yuanhua Cong; Xiaoping Zeng; Dawei Wang; Hongyang Zhao; Huinan Suo; Liu Yang; Xiaowen Ou; Hao Jiang; et al. (Chemical Engineering Journal, 2026)

Genome wide association analysis and association of genetic risk and lifestyle with upper gastrointestinal cancer among an endoscopy-screened cohort in China - Feifan He; Xianhui Ran; Hao Jiang; Zhiyuan Fan; Yueying Zhang; Jinwu Wang; Changqing Hao; Guohui Song; Yanwei Gong; Yanyan Li; Xinqing Li; Ru Chen; et al. (Science Bulletin, 2026)

Structuring oleogels with citrus fiber as the sole gelling agent: Precise modulation of the network structure via enzymatic method - Hao-ran Jiang; Jun-ru Qi (Food Hydrocolloids, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The transcriptional regulatory module MdERF2-MdSCR11 promotes ABA-mediated apple fruit ripening through synergistic repression of MdABA4-2 - Miaomiao Wang; Qizhe Li; Hao Wang; Nan Jiang; Jiale Wang; Xiaotong Hu; Yu Liu; Tuanhui Bai; Jian Jiao; JiangLi Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2026)

Strategy for optimization of auto-driven electrochemical module towards phosphorus recovery from wastewater: Performance and mechanism of electric field regulation - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Ying Chen; Qi Kuang; Yuan Liu (Journal of Cleaner Production, 2026)

Calcium-mediated modulation of ultra-low-ester pectin-gluten interactions: subunit-level mechanisms revealed using HMW-GS deletion lines and molecular dynamics simulations - Rong-ran Zhang; Ping-ping Zhang; Tian Lv; Bo Wang; Zhe Liu; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Carbohydrate Polymers, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Hyphosphere metabolic reprogramming in lipids and aromatic amino acids drives differential mycorrhizal growth promotion in trifoliate orange - Hao-Ran Jiang; Wan-Lin Fu; Ci Deng; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Uncovering pH-driven metastable transitions and thermal aggregation of HMW-GSs via all-atom molecular dynamics simulations - Tao Yang; Rong-ran Zhang; Xin-rong Lv; Tian Lv; Bo Wang; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Zhe Liu; Hao Jiang (Food Hydrocolloids, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

A multifunctional 5-fluorouracil prodrug: synthesis, biological evaluation, and antitumor mechanism investigation - Ran Zhang; Liqing Tang; Jianglong He; Guanyu Jiang; Yingfei Su; Xueping Jiang; Ping Wu; Dongyang Zhang; Sitong Chen; Hao Li; Zhongzheng Gui (Molecular Diversity, 2026)

Bioinformatics-based discovery of a new norsesquiterpenoid from agarwood targeting CHRM2 and regulating the PI3K-Akt pathway in liver cancer - Zi-Xiao Jiang; Jian Feng; Wen-Cheng Hou; Mei-Ran Wang; Shu-Nan Zhang; Hao-Jie Liang; Yang-Yang Liu (Phytochemistry Letters, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Consolidated combined V-H-M-T capacity of a suction caisson in clay - Hao Ran Li; Xiu Zhe Wang; Jiang Tao Yi; Hong Yu Tang; Xiao Han (Ocean Engineering, 2026)

Bio-based anhydride crosslinked furan-derived vitrimeric epoxy networks with intrinsic flame retardancy, self-healing capacity and recyclability - Tian-Mo Yang; Hao-Xin Niu; Wen-Jie Zheng; Hao-Ran Jiang; Yuan Hu; Xin Wang (Journal of Cleaner Production, 2026)

Towards zero liquid discharge: Resource recovery and circular economy pathways via bipolar membrane electrodialysis - Hao-Ran Yang; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Ying Chen; Yuan Liu (Chemical Engineering Journal, 2026)

Optimizing housefly larval bioconversion of silkworm excrement through wheat bran Supplementation: Enhanced cellulose degradation and nutrient recovery - Chen Chen; Yuanhao Zhang; Xueming Xu; Xueping Jiang; Jieling Zhou; Jia Kong; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Asia-Pacific Entomology, 2025)

Regulation of phytoplankton community by mesoscale eddies and the East Indian Coastal Current in the southwestern Bay of Bengal during the northeast monsoon - Hao Chen; Yuanli Zhu; Lihua Ran; Mengjia Zhang; Xiao Ma; Hongliang Li; Feng Zhou; W.N.C. Priyadarshani; Zhibing Jiang (Marine Environmental Research, 2025)

Unraveling mulberry anthocyanins’ antioxidant mechanism and biosafety via computational modeling - Jianglong He; Yuqi Li; Xueping Jiang; Haoran Huang; Yue Zhang; Ran Zhang; Hao Li; Zhongzheng Gui (Food Bioscience, 2025)

Characterization of particle number size distribution and new particle formation in a highly-humid megacity Wuhan, central China - Haoqian Wang; Xiaoxiao Li; Jin Wu; Hao Wu; Yiran Li; Chong Liu; Ning Ma; Ping Zeng; Xuehui He; Jiapeng Ran; Huaying Song; Dandan Huang; et al. (Atmospheric Environment, 2025)

Comparative Genomics Uncovers Molecular Adaptations for Cetacean Deep‐Sea Diving - Fan Zhang; Tong Zhang; Hao Dong; Jie Jiang; Guang Yang; Inge Seim; Ran Tian (Molecular Ecology, 2025)
Cetaceans show remarkable diversity in diving capability, implying a range of adaptive strategies to hazards such as hydrostatic pressure and oxidative stress, but few studies have considered the evolution of extreme diving. Here, we first examined the relationship between morphological and physiological factors and diving capability and then considered the molecular evolution of candidate deep‐sea diving traits in a genomic dataset of cetaceans. Our dataset included six super‐divers, sperm whales (families Physeteridae and Kogiidae) and beaked whales (Ziphiidae), species that can dive deeper than 1000 m for about an hour or longer. We found a positive association between diving capability and oxygen‐linked globins, and super‐diver myoglobin ( MB ) is under positive selection and harbours a reported functional amino acid change. Blubber thickness was positively associated, likely to provide thermal insulation and hydrostatic pressure resistance. Super‐divers have gene changes that may contribute to differences in the composition of outer blubber neutral lipids (triacylglycerols and wax esters), fatty acids and cholesterol. Total lung capacity relative to body mass showed a negative association, ostensibly to limit gas bubbles that can cause decompression sickness. A functional assay suggests that an ATP8B1 amino acid substitution may reduce lung injury in super‐divers. Super‐diver XDH has two unique amino acids and a decreased ability to produce uric acid under hypoxia when its ROS‐generating XO isoform is prevalent, suggesting that it reduces cell damage from oxidative stress and uric acid accumulation in species with prolonged dives. Our study deepens the understanding of how deep‐sea diving emerged in the cetacean lineage.

Curcumin-mediated photodynamic treatment efficiently inhibits Bacillus cereus and extends the shelf-life of flat rice noodles - Hao-Ran Ji; Jia-Jun Yan; Zi-Hui Chen; Wen-Li Shi; Li-Wen Chen; Juan Wang; Yu Ding; Ai-Min Jiang; Bing Du; Cai-Hu Liao; Hong-Tao Lei; Quan Zhou; et al. (Food Research International, 2025)

Nitrogen cycling and ecological impacts mediated by water mass interactions in the Yangtze river estuary and the adjacent east China Sea: insights from nitrogen and oxygen isotopes - Ziying Zhou; Zhi Yang; Bin Wang; Haiyan Jin; Lihua Ran; Zhibing Jiang; Qianna Chen; Feng Zhou; Hao Zheng; Jianfang Chen (Continental Shelf Research, 2025)

Synergistic coupling of bipolar membrane electrodialysis and Fenton process for sustainable management of landfill leachate reverse osmosis concentrate - Hao-Ran Yang; Changjiang Li; Chiqian Zhang; Xiaohong Lan; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng; Zhi-Hua Yuan (Chemical Engineering Journal, 2025)

Genomic and transcriptomic insights into the cellulose-degrading mechanism of Bacillus subtilis DC-11 and its novel cellulose catabolic pathway - Chen Chen; Minqi Zhang; Yuanhao Zhang; Xueping Jiang; Jia Kong; Jieling Zhou; Gaiqun Huang; Ran Zhang; Hao Li; Zhongzheng Gui (Archives of Microbiology, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

A novel ciprofloxacin-degrading bacteria Phytobacter diazotrophicus SMX isolated from silkworm faeces: characteristics, degradation metabolites, and toxicity assessment - Jia Kong; Xueping Jiang; Yuqi Li; Jielin Zhou; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Asia-Pacific Entomology, 2025)

Glycosidase inhibitory isoflavones from the seeds of Cullen corylifolium and their structure–activity relationship study - Ying-Xiao Xiao; Yi-Ran Jiang; Wen-Hui Xu; Yuan Gao; Tian-Tian Bei; Hao Xu; Xue-Feng Wu; Hyun-Sun Lee; Long Cui (Natural Product Research, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Experimental and numerical investigations on fluid resonance in moonpool affected by the side wall reflection - Hao Liu; Sheng-Chao Jiang; Ya-Qing Ran; Zi-Hao Wang; Zhi-Wei Song (Ocean Engineering, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Effects of agricultural plastic films on crop growth and soil health in tobacco fields: A comparative study - Hao Xia; Jia Shen; Muhammad Riaz; Fafen Ran; Tingming Cheng; Xueying Wang; Qing Dong; Chaolong Zu; Bo Liu; Saba Babar; Chaoqiang Jiang (Applied Soil Ecology, 2025)

Comprehensive analysis of biotransformation pathways and products of chloramphenicol by Raoultella Ornithinolytica CT3: Pathway elucidation and toxicity assessment - Xueping Jiang; Hao Li; Jia Kong; Yuqi li; Xiangdong Xin; Jielin Zhou; Ran Zhang; Kwang Sik Lee; Byung Rae Jin; Zhongzheng Gui (Journal of Hazardous Materials, 2024)

Alterations in the nutrient composition, muscle quality, and proteomics of two Sepiidae species (Sepiella maindroni and Sepia esculenta) during storage - Shan-Shan Jiang; Hao-Ran Lv; Hui-Min Lin; Jie Feng; Soottawat Benjakul; Shucheng Liu; Bin Zhang (Food Bioscience, 2024)

Advanced electrochemical membrane technologies for near-complete resource recovery and zero-discharge of urine: Performance optimization and evaluation - Hao-Ran Yang; Yuan Liu; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Chuan Wang; Hong Liu (Water Research, 2024)

Tsuga leaves from the Neogene Baoshan Basin in southwest China and their palaeoecological implications - Hao-Ran Zong; Jin-Jin Hu; Nian Wang; Yong-Jiang Huang (Geobios, 2024)

Whole Genome Sequencing Analysis of Cellulose-degrading Bacterium DC11 Isolated from Silkworm Excrement and Characterization of Its Key Cellulase Gene ytoP - Yuanhao Zhang; Hao Li; Minqi Zhang; Xueping Jiang; Chen Chen; Xiaohui Zhang; Ran Zhang; Gaiqun Huang; Gang Liu; Zhongzheng Gui (Journal of Asia-Pacific Entomology, 2024)

Studies on 1-deoxynojirimycin biosynthesis in mulberry ( Morus alba L.) seeds through comparative transcriptomics - Xiangdong Xin; Xueping Jiang; Attaribo Thomas; Baoxin Niu; Minqi Zhang; Xueming Xu; Ran Zhang; Hao Li; Zhongzheng Gui (Natural Product Research, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Influence of the community assemblage on sulfur distributions in the South China sea - Hao-Quan Zhang; Juan Yu; Jing-Guang Lai; Gui-Peng Yang; Long-Fei Liu; Yu Jiang; Xin-Ran Song; Yong-Qiao Chen; Hou-Jin Zhou; Qi Zhang (Marine Environmental Research, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Construction of dual functional CuAl-LDHs nanocomposite loaded with IGF2BP3 siRNA for enhanced therapy of gastric cancer - Haiping Li; Yuying Zhang; Bo Huang; Feifei Yang; Qiang Ma; Xiaolin Wang; Yuying Liu; Junwu Ren; Xiaojuan Pan; Ce Liang; Shimin Wang; Hao Ning; et al. (Chemical Engineering Journal, 2024)

Triblock polymer PDMAEMA-co-PNIPAM-co-PMPC to deliver siKRAS for gene therapy in pancreatic cancer - Lidong Cao; Mengmeng Dong; Kai Jiang; Qing Zhu; Feng Li; Zunqiang Xiao; Hao Tang; Ran Tao (Chemical Engineering Journal, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Estimation of sequential transient flow around cylinders using recurrent neural network coupled graph convolutional network - Hao-Ran Xie; Yue Hua; Yu-Bai Li; Nadine Aubry; Wei-Tao Wu; Yong He; Jiang-Zhou Peng (Ocean Engineering, 2024)

Study on characterization and distribution of four regions of tight sandstone condensate gas reservoirs in the depletion development process - Xiliang Liu; Hao Chen; Zhihai Chen; Ran Yang; Liyang Song; Mingxing Bai; Ping Qiu; Mingsheng Zuo; Borui Li; Baoxi Yang; Xuankai Jiang; Yuting Wu; et al. (Fuel, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Recovery of carbon from spent carbon cathode by alkaline and acid leaching and thermal treatment and exploration of its application in lithium-ion batteries - Hao Zhou; Dayong Zhang; Yongjun Jiang; Bo Zeng; Chenxi Zhao; Mingjie Zhang; Baiyan Zeng; Xiaoquan Zhu; Xintai Su; Valentin Romanovski; Ran Bi (Environmental Science and Pollution Research, 2023)

Waste-treating-waste: Upcycling discarded polyester into metal–organic framework nanorod for synergistic interfacial solar evaporation and sulfate-based advanced oxidation process - Huiying Bai; Panpan He; Liang Hao; Zifen Fan; Ran Niu; Tao Tang; Jiang Gong (Chemical Engineering Journal, 2023)

Shape-controlled fabrication of MnO/C hybrid nanoparticle from waste polyester for solar evaporation and thermoelectricity generation - Zifen Fan; Jiaxin Ren; Huiying Bai; Panpan He; Liang Hao; Ning Liu; Bingyu Chen; Ran Niu; Jiang Gong (Chemical Engineering Journal, 2023)

Prenylaromadendrane-type diterpenoids from the gum resin of Boswellia sacra flueck and their cytotoxic effects - Jia-Jia Wang; Xin-Yue Suo; Hao-Ran Sun; Xue Wang; Ming-Bao Lin; Jin-Hua Wang; Jian-Dong Jiang; Teng-Fei Ji (Natural Product Research, 2022)

The effect and attributable risk of daily temperature on category C infectious diarrhea in Guangdong Province, China - Qiang Hao; Qi Gao; Ran Zhao; Haitao Wang; Hao Li; Baofa Jiang (Environmental Science and Pollution Research, 2022)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

A genome-wide association study on growth traits in orange-spotted grouper (Epinephelus coioides) with RAD-seq genotyping - Hui Yu; Xinxin You; Jia Li; Xinhui Zhang; Shuai Zhang; Shoujia Jiang; Xueqiang Lin; Hao-Ran Lin; Zining Meng; Qiong Shi (Science China Life Sciences, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

COMP-Ang1 promotes long-term survival of allogeneic islet grafts in a bioinert perforated chamber by inhibiting inflammation via inhibition of the TLR4 signaling pathway - Dalei Wang; Lina Jiang; Yingzi Liang; Xiaoyan Hao; Chen Chen; Wei Xia; Ran Zhuang; Yingjun Su; Shuzhong Guo (Biotechnology Letters, 2016)

Temporal and spatial distributions of sodium and polyamines regulated by brassinosteroids in enhancing tomato salt resistance - Qingsong Zheng; Jinlong Liu; Ran Liu; Hao Wu; Chaoqiang Jiang; Changhai Wang; Yongxiang Guan (Plant and Soil, 2016)

Subliminal trauma reminders impact neural processing of cognitive control in adults with developmental earthquake trauma: a preliminary report - Xue Du; Yu Li; Qian Ran; Pilyoung Kim; Barbara L. Ganzel; GuangSheng Liang; Lei Hao; Qinglin Zhang; Huaqing Meng; Jiang Qiu (Experimental Brain Research, 2016)

Mucor irregularis Infection Around the Inner Canthus Cured by Amphotericin B: A Case Report and Review of Published Literatures - Daoxian Kang; Xian Jiang; Huiying Wan; Yuping Ran; Dan Hao; Chaoliang Zhang (Mycopathologia, 2014)

A two-dimensional electrophoresis reference map of human ovary - Lei Wang; Ye-Fei Zhu; Xue-Jiang Guo; Ran Huo; Xiang Ma; Min Lin; Zuo-Min Zhou; Jia-Hao Sha (Journal of Molecular Medicine, 2005)